Preparation method of ultrathin lithium foil

By removing the passivation layer and forming a protective layer during the preparation of lithium foil, the problems of difficulty in preparing ultra-thin lithium foil and poor electrical performance are solved, and efficient and stable preparation of ultra-thin lithium foil is achieved.

CN119685741APending Publication Date: 2025-03-25HEFEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411925894.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing ultra-thin lithium foils with thickness of less than 20 μm have problems such as difficult preparation, difficult to store for a long time, and poor electrical performance.

Method used

By heating and melting the lithium ingot, coating on the substrate and cooling, the surface passivation layer is removed, covered with a PET film and rolled on the roll, an ultra-thin lithium foil with a thickness of less than or equal to 20 μm, and a protective layer is formed on the surface of the material to improve stability.

Benefits of technology

The uniformity and flawlessness of ultra-thin lithium foil are achieved, which reduces the difficulty of preparation, improves electrical performance and storage stability, simplifies the production process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of an ultrathin lithium foil, and relates to the technical field of lithium batteries. The preparation method of the ultrathin lithium foil at least comprises the following steps: heating and melting a lithium ingot to obtain molten lithium; coating a base material with the molten lithium, and cooling to obtain a lithium foil; the lithium foil is placed in a polishing solution to be cleaned, and the lithium foil with the surface passivation layer removed is obtained; covering two surfaces of the lithium foil with the surface passivation layer removed with PET (polyethylene terephthalate) films, and rolling on a roller to obtain the ultrathin lithium foil; and placing the ultrathin lithium foil in a protective solution, and forming a protective layer on the ultrathin lithium foil. The ultrathin lithium foil prepared by the invention can be stored for a long time, the preparation method is simple, expensive and high-precision preparation equipment and harsh preparation conditions are not needed, and large-batch and low-cost rapid production can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for preparing an ultra-thin lithium foil. Background Art

[0002] The lithium metal anode based on reversible metal electrochemical deposition / stripping has an ultra-high theoretical capacity, which is more than 10 times the theoretical capacity of the graphite anode. It also has a low electrochemical potential and low density, and is known as the "holy grail" electrode of lithium-based batteries. The key issue in the practical application of lithium metal batteries is to improve their practical energy density. With transition metal oxide positive electrodes, lithium metal batteries can achieve extremely high energy density through appropriate battery system design. In addition, the development of lithium metal anodes has a great impact on Li-S and Li-O batteries with higher theoretical energy density. 2 Research on battery systems is also crucial.

[0003] However, the melting point of metallic lithium is low, and it has severe diffusion creep and low tensile strength at room temperature. Moreover, metallic lithium is very soft, very easy to adhere to itself, strong self-welding, and easy to stick to the roller. In order to achieve high energy density of the battery, it is necessary to develop an ultra-thin lithium foil with a thickness of less than 20μm. At present, the preparation of ultra-thin lithium foil mostly adopts the rolling process. However, due to the mechanical rolling equipment, the produced lithium foil has a large thickness tolerance, which is difficult to meet the technical indicators of the raw materials required for rolling. And when the thickness of the ultra-thin lithium foil is less than 20μm, the ultra-thin lithium foil cannot be self-supporting and needs to be attached to the support layer with substrate. Therefore, it is very important to prepare a uniform and flawless ultra-thin lithium foil less than 20μm thick. More importantly, a passivation layer will be formed on the surface of the lithium foil during the production process. During the stripping / electroplating process, this layer greatly affects the stability of the solid electrolyte interface layer (SEI) formed by the lithium foil in the electrolyte, resulting in poor electrochemical performance. Therefore, the existing ultra-thin lithium foil has the defects of being difficult to prepare, difficult to store for a long time, and poor electrical performance, which makes the use of this technology very limited. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing an ultra-thin lithium foil to solve the following technical problems: Existing ultra-thin lithium foils less than 20 μm thick have the problems of being difficult to prepare, difficult to store for a long time, and having poor electrical properties.

[0005] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing an ultrathin lithium foil comprises at least the following steps: The lithium ingot is heated and melted to obtain molten lithium; The molten lithium is coated on a substrate and cooled to obtain a lithium foil; The lithium foil is placed in a polishing liquid for cleaning to obtain a lithium foil with a surface passivation layer removed; Covering both sides of the lithium foil with the surface passivation layer removed with PET films, and rolling on a roller to obtain an ultra-thin lithium foil; The ultra-thin lithium foil is placed in a protective solution to form a protective layer on the ultra-thin lithium foil.

[0006] As a further solution of the present invention: the ultra-thin lithium foil is a self-supporting continuous strip foil with a lithium content of 90.90-99.99%, and the thickness of the ultra-thin lithium foil is less than or equal to 20 μm, and the thickness of the lithium foil is less than or equal to 50 μm.

[0007] As a further solution of the present invention: the substrate and the roller are coated with lubricating oil, and the lubricating oil is one or more of polyethylene, polyoxymethylene or silicone polymer.

[0008] As a further solution of the present invention: the preparation method of the polishing liquid at least comprises: dissolving naphthalene crystals in anhydrous tetrahydrofuran in a glove box filled with Ar to obtain the polishing liquid.

[0009] As a further solution of the present invention: the protection solution includes at least a first protection solution, and the preparation method of the first protection solution at least includes: dissolving polyvinylidene fluoride in dimethyl sulfoxide, and then adding N,N-dimethylformamide to obtain the first protection solution.

[0010] As a further solution of the present invention: the content ratio of the polyvinylidene fluoride, the dimethyl sulfoxide and the N,N-dimethylformamide is 70-80:10:1.

[0011] As a further solution of the present invention: the protective liquid also includes a second protective liquid, the second protective liquid contains a silane coupling agent, and the preparation method of the second protective liquid at least includes: adding 5% by mass of the silane coupling agent into a tetrahydrofuran solution and stirring evenly to obtain the second protective liquid.

[0012] As a further solution of the present invention: the method for preparing the protective layer comprises the following steps: placing the ultra-thin lithium foil in the first protective solution, soaking for 1-2 hours, and then heating and drying at 80-100° C. for 1-2 hours to obtain an ultra-thin lithium foil with a first protective layer; The ultra-thin lithium foil forming the first protective layer is placed in a second protective solution, immersed for 0.5-1 hour, and then heated and dried at 80-100° C. for 1-2 hours to form a second protective layer on the first protective layer.

[0013] As a further solution of the present invention: the substrate at least includes stainless steel and glass.

[0014] As a further solution of the present invention: the temperature of the rolling is 60-100° C., the speed of the rolling is 0.1-40 mm / s, and the number of rolling is 1-5 times.

[0015] Beneficial effects of the present invention: The present application uses a coating method and a rolling process to prepare an ultra-thin lithium foil with a lithium content of 90.90-99.99% and a thickness of less than 20 μm, and uses a polishing liquid to treat the surface of the lithium foil to obtain a lithium foil with a uniform surface purification, and then introduces a protective layer on the surface of the ultra-thin lithium foil through a protective liquid, thereby improving the electrical properties and storage stability of the obtained ultra-thin lithium foil, and obtaining an ultra-thin lithium foil with a uniform thickness and no defects, and no defects such as broken bands and cracks occur during the preparation process. The preparation method of the ultra-thin lithium foil provided by the present application greatly reduces the difficulty of preparing ultra-thin lithium foil, improves the production yield, simplifies the high-precision requirements of the existing rolling process, avoids the requirements for raw material technical indicators, reduces the synthesis cost, and can be prepared on a large scale.

[0016] The present application forms a first protective layer and a second protective layer on the prepared ultra-thin lithium foil, wherein the first protective layer is a LiF layer containing a lithium salt. The lithium salt in the first protective layer provides high surface energy and low surface diffusion barrier, which promotes the uniformity of Li+ flux. During the initial deposition process, lithium is uniformly deposited on the electrode surface. As the deposition time increases, lithium grows uniformly longitudinally along the electrode surface. Under the action of internal pressure, the lithium deposition morphology gradually changes to a tooth shape and is closely arranged together. The dense and uniform deposition structure effectively reduces the surface area of ​​the electrode, thereby avoiding the degree of corrosion of the electrode and improving the cycle performance and rate performance of the battery. In addition, compared with constructing a physical coating on the surface of the lithium negative electrode, the LiF layer in the present application is a first protective layer formed by an in-situ reaction, which can more effectively homogenize the flux of Li+ and ensure rapid transmission of Li+.

[0017] In the present application, the second protective layer is a silane coupling agent layer, which is formed on the first protective layer. The silane coupling agent has adhesion, scratch resistance, temperature resistance and damage resistance. The second protective layer is formed on the first protective layer. On the one hand, the adhesion of the silane coupling agent layer can ensure the peeling of the first protective layer. On the other hand, due to the scratch resistance, temperature resistance and damage resistance of the silane coupling agent layer, physical damage can be reduced, and the contact between the ultra-thin lithium foil and the air can be isolated, which can greatly improve the air stability of the ultra-thin lithium foil, so as to facilitate the long-term storage of the ultra-thin lithium foil. DETAILED DESCRIPTION

[0018] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Example 1 The preparation method of the polishing liquid comprises the following steps: 0.192 g of naphthalene crystals were added to 15 mL of anhydrous tetrahydrofuran and stirred until dissolved to obtain a polishing liquid.

[0020] The preparation method of the first protective solution comprises the following steps: 75 mg of polyvinylidene fluoride was dissolved in 15 mL of dimethyl sulfoxide, and then 1.5 mL of N,N-dimethylformamide was added to obtain a first protective solution.

[0021] The preparation method of the second protective solution comprises the following steps: 5 wt % of silane coupling agent was added into the tetrahydrofuran solution and stirred evenly to obtain a second protective solution.

[0022] All the above steps were carried out in a glove box filled with Ar gas, and the water and oxygen contents were less than 0.1 ppm.

[0023] Embodiment 2 The preparation method of the first protective liquid comprises the following steps: 80 mg of polyvinylidene fluoride was dissolved in 15 mL of dimethyl sulfoxide, and then 1.5 mL of N,N-dimethylformamide was added to obtain a first protective solution.

[0024] All the above steps were carried out in a glove box filled with Ar gas, and the water and oxygen contents were less than 0.1 ppm.

[0025] Example 3 The preparation method of ultra-thin lithium foil comprises the following steps: The lithium ingot is placed in a stainless steel bowl and heated on a heating table at 200°C until it is molten to obtain molten lithium; On a 200°C heating table, the molten lithium obtained above was poured onto a 20mm thick stainless steel substrate coated with a layer of lubricating oil, and the molten lithium was evenly coated on the substrate using a 50μm single-sided preparation device, and naturally cooled to room temperature to obtain lithium foil, and then the lubricating oil was sprayed on the surface of the substrate, and the lithium foil on the surface of the substrate was slowly removed using a stainless steel shovel and tweezers with plastic heads; The lithium foil peeled off is placed in the polishing solution prepared in Example 1 and soaked for 2 minutes, the lithium foil with the surface passivation layer removed is taken out, and the lithium foil is rinsed in anhydrous dimethyl carbonate to wash away the naphthalene salt remaining on the surface, and then the lithium foil with the surface passivation layer removed is naturally dried; A layer of lubricating oil is applied to the roller surface of the heated electric vertical roller mill, and then the upper and lower surfaces of the lithium foil with the surface passivation layer removed are covered with PET films, and the foil is horizontally fed into the roller mill heated at 80° C. for rolling 1-5 times until the thickness of the lithium foil is less than or equal to 20 μm as measured by a thickness gauge, and then naturally cooled to room temperature to obtain an ultra-thin lithium foil; The ultra-thin lithium foil was placed in the first protective solution prepared in Example 1 and immersed for 2 hours, and then taken out and placed on a stainless steel substrate and heated and dried at 100° C. for 1 hour to form a first protective layer on the surface of the ultra-thin lithium foil; The ultra-thin lithium foil with the first protective layer formed on the surface is immersed in a second protective solution for 0.5 h, taken out and placed on a stainless steel substrate and heated and dried at 100° C. for 1 h to form a second protective layer on the first protective layer, thereby completing the preparation of the ultra-thin lithium foil.

[0026] All the above steps were carried out in a glove box filled with Ar gas, and the water and oxygen contents were less than 0.1 ppm.

[0027] Example 4 The preparation method of ultra-thin lithium foil comprises the following steps: The lithium ingot is placed in a stainless steel bowl and heated on a heating table at 200°C until it is molten to obtain molten lithium; On a 200°C heating table, the molten lithium obtained above was poured onto a 20mm thick stainless steel substrate coated with a layer of lubricating oil, and the molten lithium was evenly coated on the substrate using a 50μm single-sided preparation device, and naturally cooled to room temperature to obtain lithium foil, and then the lubricating oil was sprayed on the surface of the substrate, and the lithium foil on the surface of the substrate was slowly removed using a stainless steel shovel and tweezers with plastic heads; The lithium foil peeled off is placed in the polishing solution prepared in Example 1 and soaked for 2 minutes, the lithium foil with the surface passivation layer removed is taken out, and the lithium foil is rinsed in anhydrous dimethyl carbonate to wash away the naphthalene salt remaining on the surface, and then the lithium foil with the surface passivation layer removed is naturally dried; A layer of lubricating oil is applied to the roller surface of the heated electric vertical roller mill, and then the upper and lower surfaces of the lithium foil with the surface passivation layer removed are covered with PET films, and the foil is horizontally fed into the roller mill heated at 80° C. for rolling 1-5 times until the thickness of the lithium foil is less than or equal to 20 μm as measured by a thickness gauge, and then naturally cooled to room temperature to obtain an ultra-thin lithium foil; The ultra-thin lithium foil was immersed in the first protective solution prepared in Example 2 for 2 hours, taken out and placed on a stainless steel substrate, and heated and dried at 100° C. for 1 hour to form a first protective layer on the surface of the ultra-thin lithium foil; The ultra-thin lithium foil with the first protective layer formed on the surface is immersed in a second protective solution for 0.5 h, taken out and placed on a stainless steel substrate and heated and dried at 100° C. for 1 h to form a second protective layer on the first protective layer, thereby completing the preparation of the ultra-thin lithium foil.

[0028] All the above steps were carried out in a glove box filled with Ar gas, and the water and oxygen contents were less than 0.1 ppm.

[0029] Comparative Example 1 Compared with Example 3, in Comparative Example 1, the preparation of the ultra-thin lithium foil is completed only after the first protective layer is formed on the ultra-thin lithium foil in Example 3, and the second protective layer is not formed on the first protective layer. The remaining components and preparation method are completely consistent with Example 4.

[0030] Comparative Example 2 Compared with Example 3, in Comparative Example 1, the only difference is that after the ultra-thin lithium foil is obtained by rolling in Example 3, the ultra-thin lithium foil is immersed in a second protective liquid to form a second protective layer, that is, the first protective layer is not formed, and the second protective layer is directly formed on the ultra-thin lithium foil to complete the preparation of the ultra-thin lithium foil. The remaining components and preparation method are exactly the same as those in Example 4.

[0031] Comparative Example 3 Compared with Example 3, in Comparative Example 1, the preparation of the ultra-thin lithium foil is completed only after the ultra-thin lithium foil is obtained by rolling in Example 3, and the first protective layer and the second protective layer are not formed on the ultra-thin lithium foil. The remaining components and preparation method are completely consistent with Example 4.

[0032] Battery assembly and testing In order to test the electrochemical properties and battery performance of the prepared modified current collector, the present application assembled and tested Li-Li batteries. The batteries assembled in the present application were assembled using CR 2032 button batteries. Celgard 2400 was used as the separator of the battery, and the standard ether electrolyte (1M LiTFSI in DOL / DME v / v=1:1, 2% mass fraction of LiNO 3 As an additive) as the electrolyte, the amount of electrolyte added was 40 μL.

[0033] The assembly of the Li-Li battery first places the positive electrode shell, places the lithium sheet which is the ultra-thin lithium foil prepared in Examples 3-4 and Comparative Examples 1-3 on the positive electrode shell, drips the electrolyte, and then covers the diaphragm on the lithium sheet, and then drips the electrolyte, and then places the lithium sheet on the diaphragm, and then stacks the gasket, spring sheet, and negative electrode shell in order. Finally, the battery is packaged. The assembly operation is carried out in a glove box, wherein the water molecule content is less than 0.1ppm and the oxygen content is less than 0.1ppm.

[0034] The LAND battery test system was used to test the electrochemical performance of the battery prepared by the ultra-thin lithium foil prepared by the preparation method of Examples 3-4 and Comparative Examples 1-3. The voltage test range was 0.01-3.0V and the test temperature was 25°C. The test results are shown in the table below:

[0035] It can be seen from the table that the battery prepared using the ultrathin lithium foil obtained in Examples 3-4 of the present application as an electrode has good cycle performance and rate performance. The ultrathin lithium foil prepared in Comparative Example 1 contains only the first protective layer, the ultrathin lithium foil prepared in Comparative Example 2 contains only the second protective layer, and the ultrathin lithium foil prepared in Comparative Example 3 does not contain the first protective layer and the second protective layer. The battery prepared with the ultrathin lithium foil obtained in Examples 1-3 has high rate performance, and the gram capacity can still reach 185mAh / g after 70 cycles, and the capacity retention rate can reach 95%, and the capacity retention rate of the ultrathin aluminum foil can still reach more than 85% after 70 cycles after being placed at room temperature for 30 days. However, for Comparative Examples 2 and 3, the capacity retention rates are extremely low. For Comparative Examples 1 and 3, after the ultra-thin lithium foil is placed at room temperature for 30 days, the capacity retention rates drop significantly after 70 cycles, indicating that the first protective layer provided on the ultra-thin lithium foil in the present application can improve the cycle performance and rate performance of the battery, and the second protective layer greatly prolongs the air stability of the ultra-thin lithium foil.

[0036] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing an ultrathin lithium foil, characterized in that: At least the following steps are included: The lithium ingot is heated and melted to obtain molten lithium; The molten lithium is coated on a substrate and cooled to obtain a lithium foil; The lithium foil is placed in a polishing liquid for cleaning to obtain a lithium foil with a surface passivation layer removed; Covering both sides of the lithium foil with the surface passivation layer removed with PET films, and rolling on a roller to obtain an ultra-thin lithium foil; The ultra-thin lithium foil is placed in a protective solution to form a protective layer on the ultra-thin lithium foil.

2. The method for preparing an ultra-thin lithium foil according to claim 1, characterized in that: The ultra-thin lithium foil is a self-supporting continuous strip foil material with a lithium content of 90.90-99.99%, and the thickness of the ultra-thin lithium foil is less than or equal to 20 μm, and the thickness of the lithium foil is less than or equal to 50 μm.

3. The method for preparing an ultra-thin lithium foil according to claim 1, characterized in that: The substrate and the roller are coated with lubricating oil, and the lubricating oil is one or more of polyethylene, polyoxymethylene or silicone polymer.

4. The method for preparing an ultra-thin lithium foil according to claim 1, characterized in that: The preparation method of the polishing liquid at least comprises: dissolving naphthalene crystals in anhydrous tetrahydrofuran in a glove box filled with Ar to obtain the polishing liquid.

5. The method for preparing an ultra-thin lithium foil according to claim 1, characterized in that: The protection liquid at least includes a first protection liquid, and the preparation method of the first protection liquid at least includes: dissolving polyvinylidene fluoride in dimethyl sulfoxide, and then adding N,N-dimethylformamide to obtain the first protection liquid.

6. The method for preparing an ultra-thin lithium foil according to claim 5, characterized in that: The content ratio of the polyvinylidene fluoride, the dimethyl sulfoxide and the N,N-dimethylformamide is 70-80:10:

1.

7. The method for preparing an ultra-thin lithium foil according to claim 6, characterized in that: The protection liquid also includes a second protection liquid, which contains a silane coupling agent, and the preparation method of the second protection liquid at least includes: adding 5% by mass of the silane coupling agent into a tetrahydrofuran solution and stirring evenly to obtain the second protection liquid.

8. The method for preparing an ultra-thin lithium foil according to claim 7, characterized in that: The method for preparing the protective layer comprises the following steps: placing the ultra-thin lithium foil in the first protective solution, soaking for 1-2 hours, and then heating and drying at 80-100° C. for 1-2 hours to obtain an ultra-thin lithium foil with a first protective layer; The ultra-thin lithium foil forming the first protective layer is placed in a second protective solution, immersed for 0.5-1 hour, and then heated and dried at 80-100° C. for 1-2 hours to form a second protective layer on the first protective layer.

9. The method for preparing an ultra-thin lithium foil according to claim 1, characterized in that: The substrate at least includes stainless steel and glass.

10. The method for preparing an ultra-thin lithium foil according to claim 1, characterized in that: The temperature of the rolling is 60-100° C., the speed of the rolling is 0.1-40 mm / s, and the number of the rolling is 1-5 times.